PAPUAN EFL LEARNERS’ STRATEGIES IN ACQUIRING ENGLISH - Wael, Ahmad; Noor, Laila; Saputra, Dian; Hartanti, Rezkiah (Linguists : Journal of Linguistics and Language Teaching, 2025)
This article aims at identifying Language Learning Strategies (LLS) used by Papuan EFL Learners in acquiring English. This research adopted a quantitative research design by adapting the strategies in learning and acquiring English as EFL Learners. The instrument used was questionnaire as data source which is adopted from Min et al (2021). The research was conducted at English Education Department of Universitas Muhammadiyah Sorong West-Papua Indonesia. The participants were selected by using total sampling that the researchers took all Papuan EFL learners.  The result showed that the participants used various learning strategies to acquire English. They use Metacognitive strategies as the first rank that helps them in acquiring English. Participants tend to use self-plan and self-monitoring in regulating their own cognition toward their learning process. However, it   followed by affective strategies in the second rank. The third strategies were social strategies. The participants used cognitive strategies in fourth rank and followed by memory strategies. The last learning strategies used by participants were cognitive strategies. These findings underline the vital role of metacognitive strategies in successful language acquisition for Papuan EFL learners. The study significantly contributes to the EFL education field by offering a unique insight into the learning strategies of a previously understudied learner group. The findings carry crucial implications for educators and policymakers, informing pedagogical approaches, and guiding effective resource allocation for this demographic. Further research is encouraged to expand on these findings and explore their application in other EFL contexts.